"Arte et Labore"—A Blackburn Rovers fan's legacy in human complex trait genetics. (27th June 2019) - Visscher, Peter M.; Wray, Naomi R.; Haley, Chris S.
Abstract: Through his own research contributions on the modelling and genetic analysis of quantitative traits and through his former students and postdocs, Robin Thompson has indirectly left a major legacy in human genetics. In this short note, we highlight examples of the long‐lasting relevance and impact of Robin's work in human genetics. A lone early study of marker‐assisted selection developed many of the tools and approaches later exploited (often after reinvention) by the human genetics community in GWAS studies and for prediction. Furthermore, a particularly clear example of the pervasive impact of Robin's work is that REML has become the default method to estimate variance components and that genetic predictions exploiting linkage disequilibrium in the population are starting to become used in precision medicine applications.